Prevalence of metabolic syndrome in cirrhotics with gastric antral vascular ectasia. Issue 1 (January 2022) - Aryan, Mahmoud; Jariwala, Ravi; Alkurdi, Basem; Peter, Shajan; Shoreibah, Mohamed
Abstract: Background and aims: Gastric antral vascular ectasia (GAVE) is characterized by angliodysplastic lesions that can cause upper gastrointestinal bleeding (UGIB). The mechanism behind GAVE and its association with other diseases remains unknown. We investigated the association of metabolic syndrome in cirrhotic GAVE patients when compared to esophageal variceal hemorrhage (EVH) patients. Methods: We performed a retrospective review of 941 consecutive esophagogastroduodenoscopies (EGDs) for UGIB at a medical center between 2017 and 2019. The GAVE group consisted of EGD or biopsy diagnosed cirrhotic GAVE patients, and the EVH group consisted of EVH patients with active bleeding or stigmata of recent hemorrhage on EGD. Baseline variables including co-morbidities and cirrhotic etiology were recorded. Continuous variables were compared using Wilcoxon test and categorical variables were compared using Chi-square or Fisher's exact test. Multiple logistic regression analysis evaluated the association between GAVE and covariates. Results: The final cohort had 96 GAVE and 104 EVH patients. Mean BMI was significantly higher in the GAVE cohort (32.6 vs 27.9, p < 0.0001) in addition to diabetes, hypertension, and hyperlipidemia (53.1% vs 37.5%; 76% vs 47.1%; 38.5% vs 14.4%; respectively, all p < 0.05). Non-alcoholic steatohepatitis (NASH) cirrhosis was more prevalent in GAVE than EVH patients (50% vs 24%, p = 0.0001). Multiple logistics regression revealed female sex, increased BMI, hypertension, and hyperlipidemia all having significantly higher risk of GAVE (all p < 0.05). Conclusion: Our data indicates that when compared to cirrhotics patients with EVH, cirrhotics with GAVE have increased risk of metabolic syndrome. This may play a role in the underlying pathophysiology of GAVE. Highlights: Our data indicates that cirrhotics with GAVE may be at increased risk of metabolic syndrome. Compared to cirrhotics with EVH, GAVE cirrhotics had higher prevalence of NASH cirrhosis and overall higher BMI. GAVE cirrhotics had more co-morbidities including diabetes, hypertension, and hyperlipidemia versus EVH cirrhotics.